Why is the price of coffee rising globally? Future prospects for Ethiopian coffee - Massrie, Kelemu Dessie (Frontiers in Sustainable Food Systems, 2025)
The global coffee market has experienced significant price volatility in recent years, with rising prices influenced by multiple factors, including climate change, supply chain disruptions, increased production costs, and growing demand. This review investigates the causes of global coffee price increases, focusing on their impact on Ethiopia’s coffee sector, a major player in global production and export. Climate change, through extreme weather events, has resulted in fluctuating yields and reduced productivity, threatening the stability of Ethiopia’s coffee industry. Supply chain disruptions, including labor shortages and shipping delays aggravated by the COVID-19 pandemic, have further strained the market. Moreover, rising input costs, particularly for fertilizers and labor, have added pressure on coffee producers. While the price surge presents opportunities for increased export revenues, particularly in specialty coffee, these benefits are tempered by the challenges of climate variability, labor shortages, and rising production costs. To enhance resilience and sustain growth, Ethiopia must prioritize climate-smart agricultural practices, technological innovation, and market diversification. Government support, including infrastructure development and financial services are essential to strengthen the coffee sector’s competitiveness and ensure long-term sustainability in the face of global market fluctuations.